Functional probes for cardiovascular molecular imaging - Zeng, Yun; Zhu, Jing; Wang, Junqing; Parasuraman, Paramanantham; Busi, Siddhardha; Nauli, Surya M.; Wáng, Yì Xiáng J.; Pala, Rajasekharreddy; Liu, Gang (Quantitative Imaging in Medicine and Surgery; Vol 8, No 8 (September 30, 2018): Quantitative Imaging in Medicine and Surgery, 2018)
Cardiovascular diseases (CVDs) are a severely threatening disorder and frequently cause death in industrialized countries, posing critical challenges to modern research and medicine. Molecular imaging has been heralded as the solution to many problems encountered in individuals living with CVD. The use of probes in cardiovascular molecular imaging is causing a paradigmatic shift from regular imaging techniques, to future advanced imaging technologies, which will facilitate the acquisition of vital information at the cellular and molecular level. Advanced imaging for CVDs will help early detection of disease development, allow early therapeutic intervention, and facilitate better understanding of fundamental biological processes. To promote a better understanding of cardiovascular molecular imaging, this article summarizes the current developments in the use of molecular probes, highlighting some of the recent advances in probe design, preparation, and functional modification.